Recognition and revision of the Phelister panamensis group (Histeridae: Histerinae: Exosternini) - Caterino, Michael S.; Tishechkin, Alexey K. (Zootaxa, 2026)
Here we establish the Phelister panamensis species group, revising the eight included species (two of which are described as new). The nominate species is widely distributed in the Americas, from the US south to Argentina, and has probably expanded its distribution in association with domestic cattle, in whose dung it is often found. The group’s monophyly is strongly supported by unique hooks on the apex of the male 8th sternite. Based on previous analyses, their affinities appear to be reasonably close to other ‘core’ Phelister, including the P. haemorrhous (which holds the type of the genus) and P. pusio groups. The P. panamensis group contains the following species: Phelister panamensis J.E. LeConte 1859, Phelister acoposternus Marseul 1853, Phelister amplistrius Schmidt 1893, Phelister brevistrius Marseul 1854, Phelister pumilus Erichson 1834, Phelister muscicapa Marseul 1870, Phelister apurimac sp. nov., and Phelister foveisternus sp. nov. We also designate lectotypes for Phelister omissus Schmidt (=P. panamensis), Phelister atrolucens Casey (=P. panamensis), Phelister amplistrius Schmidt, Phelister brevistrius Marseul, Phelister muscicapa Marseul, Phelister acoposternus Marseul, Phelister parvulus Erichson (=P. acoposternus), Phelister pumilus (Erichson), and Phelister confuseanus Marseul (=P. pumilus).